Clinical utility of ultrasonography‐measured visceral adipose tissue depth as a tool in early pregnancy screening for gestational diabetes: a proof‐of‐concept study. Issue 7 (3rd May 2019) - Thaware, P. K.; Patterson, C. C.; Young, I. S.; Casey, C.; McCance, D. R.
Abstract: Aim: To examine, in a proof‐of‐concept study, the ability of visceral adipose tissue depth and subcutaneous fat depth measured in early pregnancy to predict subsequent gestational diabetes, and to assess the performance of these measures as screening tests for gestational diabetes compared with use of the current UK criteria. Methods: A total of 100 women in early pregnancy were recruited from a maternity hospital in Belfast, UK. Visceral adipose tissue depth and subcutaneous fat depth were measured, and each participant underwent a 75‐g oral glucose tolerance test at 28 weeks' gestation for the diagnosis of gestational diabetes using WHO 2013 criteria. Results: Eighty women completed the study, of whom 15 (19%) developed gestational diabetes. Increasing visceral adipose tissue depth, but not subcutaneous fat depth, was associated with greater gestational diabetes risk after adjusting for confounding factors (odds ratio for a 1‐sd rise 2.09, 95% CI 1.06–4.12; P =0.03). Visceral adipose tissue depth ≥4.27 cm had greater sensitivity compared with current National Institute of Health and Care Excellence criteria (87% vs 40%, respectively; P =0.02) and similar specificity (62% vs 74%, respectively; P =0.15) for identifying gestational diabetes. Conclusions: Ultrasonography‐measured visceral adipose tissue in early pregnancy is a potential clinical tool for improving sensitivity of selective screening for gestational diabetes, which, compared with universal oral glucose tolerance testing, is likely to reduce by half the numbers requiring this test. Further larger studies are now required for confirmation, including investigation into impact on clinical outcomes. What's new?: Current international guidelines recommend universal screening for gestational diabetes mellitus (GDM) using an oral glucose tolerance test (OGTT) at between 24 and 28 weeks' gestation, but this is labour‐intensive and expensive. The advice in current UK practice is to adopt a selective screening approach for GDM based on several risk factors, but these lack sensitivity and specificity. Visceral adipose tissue depth and subcutaneous fat depth in early pregnancy were measured to predict subsequent GDM. Increasing visceral adipose tissue depth, but not subcutaneous fat depth, was associated with greater GDM risk. Visceral adipose tissue depth ≥4.27 cm had greater sensitivity in predicting GDM compared with the current UK screening strategy.